2019
DOI: 10.1109/access.2019.2902730
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Orchid Surfaces Using Top-Down Contact Angle Mapping

Abstract: Top-down contact angle (CA) measurements are used to characterize the green leaves and purple flowers of both old and young the Cattleya warneri orchids. The top-down CA allows the characterization of large surfaces away from the leaf edge, avoiding traditional cutting required for side view CA measurement. This allows large area mapping without damaging leaves making the method amenable to fieldwork and useful in environmental diagnostics. Young leaves are found to be hydrophobic whilst old leaves become prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…If it is hydrophilic h will be less than r cap . However, if it is larger, then the volume is not correct and instead, the following volume is used to obtained h [24]: …”
Section: Methodsmentioning
confidence: 99%
“…If it is hydrophilic h will be less than r cap . However, if it is larger, then the volume is not correct and instead, the following volume is used to obtained h [24]: …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, machine learning methods like the naive Bayes method have been employed for pest and disease diagnosis in black orchid plants, demonstrating their effectiveness in automated disease detection [22]. Furthermore, advancements in surface assessment technologies, such as top-down contact angle mapping, have been explored for evaluating orchid surfaces, providing insights into plant health and growth conditions [23]. In addition, innovative ranging technologies, including height-variable monocular vision, have been developed for smart agriculture applications, enabling precise monitoring and management of crop growth [24].…”
Section: History Of Researchmentioning
confidence: 99%
“…Top-down contact angle measurements were used to measure Cattleya warneri orchids and Dracaena draco at different ages and it was observed that the older leaves showed hydrophilicity while the younger leaves showed hydrophobicity (Janeczko et al, 2019;Jura-Morawiec and Marcinkiewicz, 2020). Unique leaf structures on the surface of young leaves during their developmental stages, such as various papillae, play an important role in the increase of wettability.…”
Section: Growth Agementioning
confidence: 99%